The 20 most important questions for novices of full-endoscopic spinal surgery in China: a mixed-method study protocol - Bin Zhu; Can Liu; Hong Ling Chu; Geng Li; Jiao Yang He; Yun Long Ma; Chuan Chao Du; Bao Hai (BMJ Open)
Introduction The full-endoscopic spinal surgery (FESS) procedure is widely accepted and welcomed in China. With the continuous development of minimally invasive surgery, the further expansion of indications and the greater diversity of techniques, spinal endoscopic surgery currently accounts for more than 10% of spinal surgery in China, ranking among the top in the world. However, the admission system and standardised training system for spinal endoscopic surgery are not perfect, which presents a challenge and disadvantage for novices.Methods and analysis Exploratory mixed methods are applied for designing this study. First, we will collect questions from novices by allowing them to openly list their concerns to those who have completed FESS. These qualitative questions will be categorised using NVivo software. To produce the qualitative results, a questionnaire for the sequential two-round Delphi approach will be developed to identify the 20 most important questions from novices. This study is planned to be started at April 2021, and completed at March 2022.Ethics and dissemination The Research Ethics Committee of Peking University Third Hospital provided a waiver for this Delphi protocol. We expect that the findings will be published in a clinical journal and presented at conferences. Furthermore, we hope that the results can contribute to answering the questions raised by novices of spinal endoscopy in the form of books and to improving the training system for spinal endoscopy surgery.